2022
DOI: 10.1111/jcal.12747
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of students' collaborations by variations in their learning orientations in blended course designs: How is it associated with academic achievement?

Abstract: Background While a number of learner factors have been identified to impact students' collaborative learning, there has been little systematic research into how patterns of students' collaborative learning may differ by their learning orientations. Objectives This study aimed to investigate: (1) variations in students' learning orientations by their conceptions, approaches, and perceptions; (2) the patterns of students' collaborations by variations in their learning orientations and (3) the contribution of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…They share and pursue common interests and achieve common goals (Zarzour et al, 2020). Online learners' interactive behaviours can significantly affect their learning performance (Goggins & Xing, 2016; Han et al, 2022; Li & Tsai, 2017). The study found that the group which exhibits more discussion behaviours tend to have higher collaborative performance (Hwang et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They share and pursue common interests and achieve common goals (Zarzour et al, 2020). Online learners' interactive behaviours can significantly affect their learning performance (Goggins & Xing, 2016; Han et al, 2022; Li & Tsai, 2017). The study found that the group which exhibits more discussion behaviours tend to have higher collaborative performance (Hwang et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the present study only used one type of observational log data-frequency to examine students' observed study approaches. The advancement of learning analytics functions has made it possible to record a diversity of types of log data, such as time spent on different types of online learning activities (duration), the exact time at which a logged event occurs (timestamp), and the sequences of online events (sequence) [22,[57][58][59]. Therefore, future studies may employ multiple types of log data to examine students' observed study approaches [49,50].…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…However, fully relying on the observational log data to examine students' study approaches without guidance from educational theories has also received criticism of being data-centric, which could result in erroneous interpretations due to a lack of sound theories and meaningful contexts [20]. To address the drawbacks of the self-reported and observational log data, in recent years, researchers have begun to employ both self-reported and observational log data to understand students' study approach [21][22][23][24]. The present investigation will adopt Student Approaches to Learning research as a theoretical framework and will use both self-reported and observational log data to examine students' study approaches in flipped classroom courses.…”
Section: Introductionmentioning
confidence: 99%